2(9s+2)-10s=2(4s+1)-3

Simple and best practice solution for 2(9s+2)-10s=2(4s+1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(9s+2)-10s=2(4s+1)-3 equation:


Simplifying
2(9s + 2) + -10s = 2(4s + 1) + -3

Reorder the terms:
2(2 + 9s) + -10s = 2(4s + 1) + -3
(2 * 2 + 9s * 2) + -10s = 2(4s + 1) + -3
(4 + 18s) + -10s = 2(4s + 1) + -3

Combine like terms: 18s + -10s = 8s
4 + 8s = 2(4s + 1) + -3

Reorder the terms:
4 + 8s = 2(1 + 4s) + -3
4 + 8s = (1 * 2 + 4s * 2) + -3
4 + 8s = (2 + 8s) + -3

Reorder the terms:
4 + 8s = 2 + -3 + 8s

Combine like terms: 2 + -3 = -1
4 + 8s = -1 + 8s

Add '-8s' to each side of the equation.
4 + 8s + -8s = -1 + 8s + -8s

Combine like terms: 8s + -8s = 0
4 + 0 = -1 + 8s + -8s
4 = -1 + 8s + -8s

Combine like terms: 8s + -8s = 0
4 = -1 + 0
4 = -1

Solving
4 = -1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8v+1=1-8v | | 2y=-7x+8 | | 7x+11y=16 | | 8(x+6)+3=51 | | (2xy-3x^2)dx+(x^2+y)dy=0 | | -(5y+2)-(-4y-4)=-2 | | 161+51(6)= | | y=1.90x+3.90 | | -16+4x=7x-5x | | 7x+11y=9 | | Xn=180(n-2) | | -5(v-4)+2=11-(v-3) | | x^2+20x+100-x^4=0 | | -5x+1+6x=-7+18 | | x^2+8x-9=-6 | | y-6+2(4y+2)=-5(y+4) | | 1.15z=61410 | | x+(x+1)+(x+2)+(x+3)+(x+4)+(x+5)=185 | | 12y=-96+8x | | 4(3a+4)-8= | | 4(4x-3)-6=12z-12-2x | | 60-5x=70-25x | | x(x-6)=14 | | -8x+2=8-6x | | -5(-3w+4)-7w=2(w-9)-5 | | (p^3-4p^2+p)-(3p^2+2p+7)=0 | | 4(a-8)=12a-6 | | 10x-4(x-6)=5x+5 | | 1v+7=13+4v | | -4(5x-6)+2=-20x+26 | | x^3y^4-y^4=0 | | (x+5)(-6)=0 |

Equations solver categories